تنوع استخدام الحروف الهجائية كنظام كتابي جديد في كتابة الخط العربي الملايوي /الخظ العربي الجاوي - Muthmainnah Choliq; Nur Hanifatus Sholeha; Fathimah Kamilatun Nisa (Universitas Negeri Malang, 2022)
The progress of the civilization is considered to be the growth of their language, both between the mktaz and the written. The use of the Arabic alphabet has become in many Islamic civilizations, where it develops and diversifies its method in order to understand the Islamic religion. Such a civilization is the development of a new written system in the life of the Malay people, called the Malay Arabic script, which is a means of transmitting Islamic knowledge and knowledge by scholars to the Muslim community in the Indonesian archipelago. There are four letters added to the Arabic letters in the Jawi letters; The letter jim with an additional two-dot variation applies like the letter “c” in Indonesian, the letter “ain” with an additional three-dot difference above the letter and marked as “ng”, the letter fa with the additional two-dot variation reading “pa”, then the letter kaf with the addition of a dot The one on top reads “ga”, the letter nun with the addition of two dots reads “nya”, and finally the letter wawu with the addition of one dot at the top reading “Va”. What is the Arabic-Malay symbol? And how its develop? Is part of discussion in this article.